On the BPS Sector in AdS3/CFT2 Holography. Issue 4 (14th February 2023) - Martinec, Emil J.; Massai, Stefano; Turton, David
Abstract: The BPS sector in A d S 3 / C F T 2 $AdS_3/CFT_2$ duality has been fertile ground for the exploration of gauge/gravity duality, from the match between black hole entropy and the CFT elliptic genus to the construction of large families of geometrical microstates and the identification of the corresponding states in the CFT. Worldsheet methods provide a tool to further explore the relation between string theory in the bulk and corresponding CFT quantities. We show how to match individual BPS strings to their counterparts in the symmetric product orbifold CFT. In the process, we find an exact match between known constructions of microstate geometries and condensates of BPS supergraviton strings, and discuss their role in the broader collection of BPS states. In particular, we explore how microstate geometries develop singularities; and how string theory resolves these singularities through the appearance of "tensionless" string dynamics, which is the continuation of structures found in the weak‐coupling CFT into the strongly coupled regime described by string theory in the bulk. We argue that such "tensionless" strings are responsible for black hole microstructure in the bulk description. Abstract : The BPS sector in A d S 3 / C F T 2 $AdS_3/CFT_2$ duality has been fertile ground for the exploration of gauge/gravity duality, from the match between black hole entropy and the CFT elliptic genus to the construction of large families of geometrical microstates and the identification of the corresponding states in the CFT. Worldsheet methods provide a tool to further explore the relation between string theory in the bulk and corresponding CFT quantities. We show how to match individual BPS strings to their counterparts in the symmetric product orbifold CFT. In the process, we find an exact match between known constructions of microstate geometries and condensates of BPS supergraviton strings, and discuss their role in the broader collection of BPS states. In particular, we explore how microstate geometries develop singularities; and how string theory resolves these singularities through the appearance of "tensionless" string dynamics, which is the continuation of structures found in the weak‐coupling CFT into the strongly coupled regime described by string theory in the bulk. We argue that such "tensionless" strings are responsible for black hole microstructure in the bulk description.